2018
DOI: 10.1126/sciadv.aaq1407
|View full text |Cite
|
Sign up to set email alerts
|

Complete enzyme set for chlorophyll biosynthesis in Escherichia coli

Abstract: Escherichia coli has been engineered to produce chlorophyll.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 40 publications
1
51
0
Order By: Relevance
“…It is possible that a large multi-enzyme assembly could channel photolabile biosynthetic intermediates between active sites, minimizing their exposure to light and oxygen. The heterologous assembly of the Chl biosynthesis pathway in E. coli provides a platform for investigating the physical and mechanistic coupling between pathway enzymes (238). This achievement also demonstrates that, after decades of research, all reactions necessary for the biosynthesis of Chl a have now been identified.…”
Section: The Transformation Of Protoix Into Chls -Chl Amentioning
confidence: 79%
“…It is possible that a large multi-enzyme assembly could channel photolabile biosynthetic intermediates between active sites, minimizing their exposure to light and oxygen. The heterologous assembly of the Chl biosynthesis pathway in E. coli provides a platform for investigating the physical and mechanistic coupling between pathway enzymes (238). This achievement also demonstrates that, after decades of research, all reactions necessary for the biosynthesis of Chl a have now been identified.…”
Section: The Transformation Of Protoix Into Chls -Chl Amentioning
confidence: 79%
“…Geranylgeranyl is incorporated into chlorophyll by ChlG in the second last step. In a landmark paper, expression of ChlDHI and GUN4, ChlM, ChlA1, LPOR, BciB, ChlG and ChlP in E. coli was sufficient for chlorophyll biosynthesis [196], demonstrating that no other enzymes are required in this pathway.…”
Section: Chlorophyll Biosynthesismentioning
confidence: 99%
“…In a recent study, heterologous expression of R. gelatinosus acsF in Escherichia coli demonstrated that cyclase activity could occur in vivo in this non-photosynthetic organism [ 3 ]. While this study suggested that any remaining parts of the enzyme are commonly present in E. coli cells, it did not fully define the essential components necessary for a completely recombinant system where all required partners are present.…”
Section: Resultsmentioning
confidence: 99%
“…Most steps for chlorophyll biosynthesis have been studied using recombinant proteins in defined reactions, but the MPE cyclase is an exception. Instead, present knowledge concerning the cyclase is based on studies using fractionated cell extracts and genetic analyses of bacteria, algae, and plants [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Two distinct enzymes have been identified that catalyze the cyclase reaction, originally distinguished by the source of the incorporated oxygen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation